الإفصاح المحاسبي و دوره في تحسين جودة المعلومات المالية - دراسة ميدانية - - سليمان, رزيق; محمد البشير, رزيق; شمس الدين, رياب; تقي الدين, فناق (University of eloued جامعة الوادي, 2022)
" هدفت الدراسة إلى التعرف على اثر الإفصاح المحاسبي على جودة المعلومات المالية و ذالك باستخدام المنهج الوصفي التحليلي عن طريق تحليل استبيان مكون من 47 عنصرا . يتكون مجتمع الدراسة من الأكاديميين و المهنيين و بلغت العينة محل الدراسة 50فردا استخدمنا البرنامج الإحصائي spss في تحليل البيانات الإحصائية و قياسها . من ابرز النتائج المتوصل إليها أن للإفصاح المحاسبي اثر ذو اتجاه ايجابي على جودة المعلومة المالية , كلما زاد مستوى جودة الإفصاح من خلال الإفصاح الكامل كانت المعلومة ذات جودة عالية و مناسبة. رفعت الدراسة توصيات أهمها الاهتمام بالإفصاح الاختياري من اجل تزويد أصحاب المصالح بمعلومات كافية ملائمة و ذات موثوقية و مصداقية معدة في قوائم و تقارير مالية معبرة بصدق عن وضعية الهيكل المالي للمؤسسة وفق مبادئ و معايير المحاسبة الدولية المتعارف عليها بما ينعكس على جودتها لإشباع رغبة مستخدميها من اجل اتخاذ قرارات هامة من اجل الحفاظ على استمرارية و نجاح المؤسسة ,تطوير معارف و مهارات معدي هذه القوائم و تطوير نظام المعلومات المحاسبية المالية ""The study aimed to identify the impact of accounting disclosure on the quality of financial information, by analyzing the results of a questionnaire consisting of 42 items. The study population is made up of academics and professionals. The sample of the study reached 50 individuals. We used SPSS statistical program. The most prominent results obtained are that the accounting disclosure has a positive impact on the quality of the financial information, that is, the higher the level of disclosure, the higher the quality of the financial information and become suitable for its users. The study made recommendations, the most important of which are: Paying attention to voluntary disclosure in order to provide stakeholders with sufficient, appropriate, reliable and credible information prepared in financial statements and reports that honestly express the result of the company’s financial position in accordance with international accounting principles and standards of general acceptance, which is reflected in its quality to satisfy The desire of its users in order to take important decisions in order to maintain the continuity and success of the company, to develop the knowledge and skills of those who prepare these lists, and to develop a favorable and accounting financial information system "
ماستر محاسبة وتدقيق
Keywords: الإفصاح المحاسبي,جودة المعلومات المالية,الإفصاح الاختياري,نظام المعلومات المحاسبية المالية: accounting disclosure, quality of financial information, voluntary disclosure, accounting financial information system